2010
DOI: 10.1016/j.biopsych.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Altered Function and Connectivity of the Medial Frontal Cortex in Pediatric Obsessive-Compulsive Disorder

Abstract: Background-Exaggerated concern for correct performance has been linked to hyperactivity of the medial frontal cortex (MFC) in adult obsessive compulsive disorder (OCD), but the role of the MFC during the early course of illness remains poorly understood. We tested whether hyperactive MFC-based performance monitoring function relates to altered MFC connectivity within task control and default mode networks in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
123
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(142 citation statements)
references
References 66 publications
(89 reference statements)
16
123
1
2
Order By: Relevance
“…The urge to perform an experimentally trained habit has been shown to be associated with hyperactivity in the caudate in OCD patients (33), whereas the vmPFC is thought to influence the caudate for goal selection (35,36). Therefore, an aberrant vmPFC valuation system as demonstrated across several tasks in OCD (5,17,37) is of critical relevance to the maintenance of the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urge to perform an experimentally trained habit has been shown to be associated with hyperactivity in the caudate in OCD patients (33), whereas the vmPFC is thought to influence the caudate for goal selection (35,36). Therefore, an aberrant vmPFC valuation system as demonstrated across several tasks in OCD (5,17,37) is of critical relevance to the maintenance of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the significance of the role of the vmPFC to estimate values to guide goal-directed behavior (12) and the interference of maladaptive vmPFC functioning in a variety of tasks in OCD (5,8,(13)(14)(15)(16)(17), we postulated that impaired vmPFC valuation would be central to the disorder. We sought to determine how patients with OCD perform on a task that is dependent on accurate and flexible value signaling by this prefrontal region.…”
mentioning
confidence: 99%
“…Existing resting-state studies in patients with OCD demonstrated altered resting-state functional connectivity in the default mode network (involving structures such as the anterior cingulate cortex and medial frontal gyrus) (Fitzgerald et al, 2010;Koç ak et al, 2012), and within the CSTC circuitry that included the fronto-striatal regions (Harrison et al, 2009;Jang et al, 2010;Stern et al, 2012). Abnormal restingstate functional connectivity between the middle cingulate cortex and parahippocampal region have also been reported in OCD, and connectivity strength between these regions was positively correlated with response inhibition deficits (Kang et al, 2013).…”
Section: Evidence Of Anomalies Using Resting-state Functional Connectmentioning
confidence: 98%
“…Of the 35 articles, 19 articles employed executive function tasks and contributed studies for inclusion in the three themes: 6 studies in Theme 1 (Response Inhibition), 11 studies in Theme 2 (Interference) and 6 studies in Theme 3 (Set-shifting/switching) (Britton et al, 2010;de Wit et al, 2012b;Fitzgerald et al, 2005Fitzgerald et al, , 2010Gu et al, 2008;Han et al, 2011;Huyser et al, 2011;Kang et al, 2013;Maltby et al, 2005;Marsh et al, 2013;Nabeyama et al, 2008;Nakao et al, 2005Nakao et al, , 2009Page et al, 2009;Remijnse et al, 2013;Roth et al, 2007;Schlosser et al, 2010;Woolley et al, 2008;Yucel et al, 2007). Notably, 2 articles employed multiple tasks and contributed studies in all three themes (Page et al, 2009;Woolley et al, 2008).…”
Section: Study 2: Executive-task Related Fmri Studiesmentioning
confidence: 99%
“…The rationale for the use of NIBS has been that if behavioral changes arising from a clinical condition occur due to altered activity within a given brain network, normalizing this activity with NIBS should lead to improved behavior. Such a rationale has motivated studies utilizing NIBS across a range of clinical conditions, including, but not limited to, stroke (Grefkes and Fink, 2014), schizophrenia (Frantseva et al, 2014), depression (Fitzgerald et al, 2009;Fox et al, 2013), and obsessive-compulsive disorder (Fitzgerald et al, 2010). Despite some encouraging results, symptomatic improvement following NIBS in such conditions has generally been modest, and often clinically insignificant (Kalu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%